Coral Fishes the Famili Chaetodontidae in Coral Reef Waters of Para Island Sub District Tatoareng, Sangihe Kepulauan Regency - Ari B. Rondonuwu; Unstain N.W.J. Rembet; Ruddy Dj. Moningkey; John L. Tombokan; Alex D. Kambey; Adnan S. Wantasen (Sam Ratulangi University, 2013)
This study aims to determine the distribution and abundance of reef fish families chaetodontidae in coral reef waters of Para Island Sub District Tatoareng. This study was conducted at 4 stations. Data collected was done using visual census on the 50-meter transect line at 5 meters depth. In addition to revealing the number of species and abundance of individuals chaetodontidae, data analysis aimed to determine number of species, individual abundance, and the community index. Based on the identification, obtained 27 species from 3 genera and 217 number of individuals.Â The highest number of species found at station Para 1.Â 7 species are always found in all observation stations, Chaetodon kleinii, C. punctatofasciatus, C. lunulatus, C. trifascialis, C. vagabundus, Heniochus varius, H. chrysostomus. The species with the largest number of individuals that is Chaetodon kleinii (45 individuals). Chaetodontidae fish species diversity index ranged between 2.207-2.866. Dominance Index are categorized low in the range of 0.078-0.122.Â Similarity index are categorized high in the range of 0.922-0.971. Keywords : coral fishes, chaetodontidae, coral reef, Para Island